Compreendendo a restrição da pesca artesanal profissional: uma relação socioeconômica em diferentes cenários na Bacia do Alto Rio Paraguai - BEATRIZ CARNEIRO DE OLIVEIRA (2022)
The Upper Paraguay River Basin (UPRB) is widely used for fishing activities and professional artisanal fishing is one of the categories present in the UPRB. Riverside communities that use fishing as a source of income and subsistence annually suffer from food and financial instability due to the fishing ban during the Piracema period - which lasts 4 months. Based on this, this work aimed to portray this type of fishing practiced in the BAP identifying the most exploited species between 1995 and 2016; as well as understanding how restriction and its socioeconomic relationships shape preference in species composition. In order to understand these dynamics, fishing data for the 22 years were compiled (available from EMBRAPA) and, later, a mathematical model based on Markov's decision process was developed. The results of the compiled data show that fishing effort in the UPRB is dictated by local markets, and therefore commercial fishing has a greater selective character than subsistence fishing. Furthermore, the result corroborates the results of the model that show that fishing effort is linked to the dependence and sensitivity of utility to fishing biomass, and therefore, it is not always advantageous to focus only on larger and more profitable species. These data may partially explain the fishing effort dynamics of artisanal professional fishing practiced by riverside communities in the Upper Paraguay River Basin.